The narrative voice in Roald Dahl’s children’s and adult books - Viñas Valle, Laura (Didáctica. Lengua y Literatura, 2008)
This article contends that Roald Dahl does not write separately and distinctly for children and adults and that differences respond mostly to the varied emphasis placed on the features that make up his books. The narrative voice that appears both in his adult and children’s books suggest continuity rather than a split in his oeuvre. My examination shows that dissimilarities between his adult and children narrators amount to the different stress he places on the features that conform to the narrative voice he constructs. Thus, depending on the way Dahl understands ‘children’s literature’ or ‘adult books’ to be, he will put more or less emphasis on these particular narrative aspects.